Structural Transformation and Hysteresis Behaviour of Ni46Cu4Mn45Sn5 Alloy Synthesized by Ball Milling Method. Issue 1 (18th December 2017) - Saini, Dinesh; Singh, Satyavir; Banerjee, M. K.; Sachdev, K.
Abstract : The present work reports synthesis and structural and magnetic studies of Ni46 Cu4 Mn45 Sn5 shape memory alloy. The synthesis was done using solid state non‐equilibrium mechanical alloying (MA) technique. MA was performed in a Pulverisette‐6 ball milling machine using Tungsten Carbide (WC) bowl and balls. Ball to powder weight ratio of 10:1 and rotation speed of 300RPM were taken as milling parameters. After 20hr milling, the obtained powder was consolidated and quenched from high temperature to induce martensitic phase transformation. X‐ray diffraction (XRD) study indicates a phase mixture of austenite and martensite phase. Variation in lattice strain and crystallite size with milling time is calculated. Microstructural study reveals dual phase mixture after quenching. Phase transformation study carried out by Differential Scanning Calorimetric (DSC) indicates martensitic phase transformation of reversible nature. Vibrating sample magnetometer (VSM) has been utilized for magnetic characterization.